Racism, xenophobia, and redistribution - Woojin Lee; John Roemer; Karine van der Straeten (University of Massachusetts, Department of Economics, 2005)
We report here a summary of our recent research on the effect that the race issue, in the United States, and the immigration issue in European countries, is having on the degree of redistribution and the size of the public sector that is implemented through political competition. We model political competition as taking place on a two dimensional policy space, where the first issue is the tax rate, or the size of the public sector, and the second issue is the race or immigration issue. Our substantive conclusion is that the conservative economic agenda has been given new life in many countries because of racist and xenophobic views of polities. JEL Categories: D3, D7, H2
Keywords: 330; Racism; xenophobia; redistribution; anti-solidarity effect; policy bundle effect; party unanimity Nash equilibrium